Clinical outcomes and prognostic factors following the surgical resection of renal cell carcinoma spinal metastases. Issue 6 (1st May 2021) - Kato, Satoshi; Demura, Satoru; Murakami, Hideki; Yoshioka, Katsuhito; Shinmura, Kazuya; Yokogawa, Noriaki; Shimizu, Takaki; Kawahara, Norio; Tsuchiya, Hiroyuki
Abstract: The efficacy of surgical resection in metastatic renal cell carcinoma is an active and important research field in the postcytokine era. Bone metastases, especially in the spine, compromise patient performance status. Metastasectomy is indicated, if feasible, because it helps to achieve the best clinical outcomes possible compared with other treatments. This study examined the postoperative survival and prognostic factors in patients who underwent metastasectomy of spinal lesions. The retrospective study included 65 consecutive patients with metastatic renal cell carcinomas who were operated on by spinal metastasectomy between 1995 and 2017 at our institution. The cancer‐specific survival times from the first spinal metastasectomy to death or the last follow‐up (≥3 years) were determined using Kaplan‐Meier analysis. Potential factors influencing survival were analyzed using Cox proportional hazard models. Planned surgical resection of all the spine tumors was achieved in all patients. Of these, 38 had complete metastasectomy of all visible metastases, including extraspinal lesions. In all patients, the estimated median cancer‐specific survival time was 100 months. The 3‐, 5‐, and 10‐year cancer‐specific survival rates were 77%, 62%, and 48%, respectively. The survival times after spinal metastasectomy were similar in both cytokine and postcytokine groups. In multivariate analyses, postoperative disability, the coexistence of liver metastases, multiple spinal metastases, and incomplete metastasectomy were significant risk factors associated with short‐term survival. Complete metastasectomy, including extraspinal metastases, was associated with improved cancer‐specific survival. Proper patient selection and complete metastasectomy provide a better prognosis in metastatic renal cell carcinoma patients. Abstract : This study examined the postoperative survival and prognostic factors in 65 metastatic renal cell carcinoma patients who underwent metastasectomy of spinal lesions. In all patients, the 3‐ and 5‐year cancer‐specific survival rates were 77% and 62%, respectively. Postoperative disability, the coexistence of liver metastases, multiple spinal metastases, and incomplete surgical resection with other existing metastases were significant risk factors associated with short‐term survival.